Ascorbic Acid Drink after Submaximal Physical Activity can Maintain the Superoxide Dismutase Levels in East Java Student Regiment - Junian Cahyanto Wibawa; Muhammad Zainul Arifin; Lilik Herawati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective - This study aimed to analyze the effect of ascorbic acid after submaximal physical activity onreducing levels of malondialdehyde (MDA) and increasing levels of superoxide dismutase (SOD) to StudentRegiment in East Java.Methods - This study was a true experiment with a randomized control group posttest-only design used 28male subjects aged 19-23 years with body mass index (BMI) 18.5-24.9 kg/m2, and randomly divided intofour groups. Namely G1 (n=7, control without submaximal physical activity+placebo), G2 (n=7, submaximalphysical activity+placebo), G3 (n=7, submaximal physical activity+AA 500 mg), and G4 (n=7, submaximalphysical activity+AA 1,000 mg). The submaximal physical activity was 2.400 meters running in 12 minutesor when the 60-70% of HRmax achieved. The drinks containing 500 mg and 1.000 mg ascorbic acid (AA)for G3 and G4 was given after exercise test. Measurement of serum MDA and SOD used the ThiobarbituricAcid Reactive Substances (TBARs) method. The data was statistical analyzed using SPSS software with asignificant level (p<0.05).Results - The results of MDA levels showed in G1 (308.18±61.81 ng/mL), G2 (338.42±125.78 ng/mL), G3(290.54±69.18 ng/mL), G4 (279.83±39.10 ng/mL) and there was no significantly difference among groups(p=0.557). The mean levels of SOD was significant among groups ((p=0.000), and the SOD level in eachgroup was G1 (23.19±0.77 units/mL), G2 (24.81±0.87 units/mL), G3 (25.27±0.79 units/mL), G4 (25.57±0.47units/mL).Conclusion - It can be concluded that 500 mg and 1.000 mg ascorbic acid drinks after submaximal physicalactivity can increase SOD levels of students regiment in East Java. Ascorbic acid drink may maintain theSOD level by lessening the use of antioxidant endogen and it may also increase the SOD level, howeverfuther research is needed to be conducted to figure out the mechamism.